2004
DOI: 10.1111/j.1469-7610.2004.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive orienting in response to eye gaze and an arrow in children with and without autism

Abstract: These results indicate that eye gaze attracted attention more effectively than the arrow in typically developed children, while children with autism shifted their attention equally in response to eye gaze and arrow direction, failing to show preferential sensitivity to the social cue. Difficulty in shifting controlled attention to the instructed side was also found in children with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
217
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(248 citation statements)
references
References 64 publications
27
217
2
2
Order By: Relevance
“…It has been shown that both children (Senju et al, 2003) and adults (Howard et al, 2000) with autism have difficulties in recognising gaze stimuli with an eye contact among serially presented averted-gaze stimuli. That the deficit is specifically related to the processing of eye contact is supported by the findings that individuals with autism can make overt discriminations of where other people are looking (Baron-Cohen et al, 1995;Kyllia¨inen & Hietanen, 2004;Leekam, Baron-Cohen, Perrett, Milders, & Brown, 1997;Tan & Harris, 1991) and that seeing of another person's averted gaze direction triggers an automatic shift of visual attention comparably in the clinical and control groups (Chawarska, Klin, & Volkmar, 2003;Kyllia¨inen & Hietanen, 2004;Senju, Tojo, Dairoku, & Hasegawa, 2004;Swettenham, Condie, Campbell, Milne, & Coleman, 2003).…”
mentioning
confidence: 89%
“…It has been shown that both children (Senju et al, 2003) and adults (Howard et al, 2000) with autism have difficulties in recognising gaze stimuli with an eye contact among serially presented averted-gaze stimuli. That the deficit is specifically related to the processing of eye contact is supported by the findings that individuals with autism can make overt discriminations of where other people are looking (Baron-Cohen et al, 1995;Kyllia¨inen & Hietanen, 2004;Leekam, Baron-Cohen, Perrett, Milders, & Brown, 1997;Tan & Harris, 1991) and that seeing of another person's averted gaze direction triggers an automatic shift of visual attention comparably in the clinical and control groups (Chawarska, Klin, & Volkmar, 2003;Kyllia¨inen & Hietanen, 2004;Senju, Tojo, Dairoku, & Hasegawa, 2004;Swettenham, Condie, Campbell, Milne, & Coleman, 2003).…”
mentioning
confidence: 89%
“…Children with ASD (ages [9][10][11][12][13][14] are slower at detecting direct gaze relative to controls [53] even though they decode and orient to the direction of averted gaze accurately [53,54]. Consistent with deficits in reciprocal gaze behavior, the results of a recent study showed that adults with ASD typically spend less time looking at the inner features of the face, particularly the eyes, in contrast to healthy or IQ matched controls [55].…”
Section: Anomalous Gaze Processing Among Children and Adults With Autismmentioning
confidence: 99%
“…Although individuals with autism demonstrate deficits in coordinating visual attention with others (i.e., joint attention) and understanding the mental states of others on the basis of information gathered from the eyes (e.g., Loveland & Landry, 1986;Mundy, Sigman, Ungerer, & Sherman, 1986;Baron-Cohen, 1995;Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001), such deficits in gaze processing do not appear to be based in eye gaze direction discrimination per se. Baron-Cohen (1995) demonstrated that such deficits appear to be characterized by impairments in using gaze to understand the mental states of others, and recent behavioral studies confirms that automatic attentional shifts in responses to static gaze direction are intact in individuals with autism (Kylliainen & Hietanen, 2004;Senju, Tojo, Dairoku, & Hasegawa, 2004;Ames & Jarrold, 2006;Bayliss & Tipper, 2005;Burgos, Kaplan, Foss-Feig, Kenworthy, Gilotty, Lee, Girton, Gaillard, & Vaidya, 2005). This pattern of findings suggests that autism is not characterized by deficits in reflexive attention orienting to gaze direction.…”
Section: Introductionmentioning
confidence: 99%